Challenges and opportunities of AI-assisted learning: a systematic literature review on the impact of ChatGPT usage in higher education - Pari-Bedoya, Ilda Nadia Monica de la Asuncion (2023)
In recent years, ChatGPT has become a noteworthy subject in the educational field due to the popularity it gained among students all over the world. Applications such as text creation, data processing, and curriculum development, among other applications, prove that ChatGPT is one of the most advanced chatbots available, albeit it posing a series of challenges that prevents students from developing their critical thinking skills in some cases. In this sense, this study’s objective is to analyze the current literature regarding the use of ChatGPT in higher education. The study questions its usage, the overall impact it has on education, and the challenges and opportunities of artificial intelligence- (AI) assisted learning, all within the research area of digital education. For this, a systematic literature review (SLR) was conducted across multiple journal databases, analyzing the articles found and filtering them with the use of specific criteria. The results of this analysis afforded the conclusion that that ChatGPT can potentially enhance both academic- and librarianrelated processes, although it is important to reconsider the ethics of using technology such as this. This is because this kind of AI technology also has the potential to modify the way people take on different jobs, tasks, and processes at an academic level, for which the correct and responsible use of ChatGPT needs to be assessed in the field of higher education.